Analysis of the Attitude of Hungarian HR Professionals to Artificial Intelligence - Karacsony, Peter (Naše gospodarstvo/Our economy, 2022)
Human resource (HR) management is one of an organisation’s most important core activities. As new technologies and software applications spread, it is important to recognise that human resource management must also mature and, to this end, must apply new technological guidelines. Artificial intelligence (AI) is one such promising technology trend that is likely to change the existing methods of HR management. This paper examines the attitudes that AI evokes among practicing HR professionals and assesses the potential for the practical application of these technologies. A survey, in the form of a questionnaire, was conducted among Hungarian HR managers, which allowed the collection of first-hand data. The survey was conducted in winter 2021 using the snowball method sampling procedure. The questionnaire mainly contained Likert-scale questions. The results of the research show that survey participants have mixed emotions about AI. The respondents largely agreed that the tools provided by AI are effective and their use helps HR management. The main limitation of the research is that it is limited to just one country, since the COVID-19 pandemic made it difficult to find and involve respondents in the research.